RANCANG BANGUN ALAT BANTU FIKSASI PADA PEMERIKSAAN WEIGHT BEARING BILATERAL KNEE JOINT DI INSTALASI RADIOLOGI RSU MUHAMMADIYAH SITI AMINAH BUMIAYU - Muhamad Ari Gufron,; Fisnandya Meita Astari,; Djoko Sukwono, (Journal of Innovation Research and Knowledge, 2025)
Background: The knee joint is part of the lower extremity that connects the upper leg to the lower leg. It is the largest and most complex joint in the body. Osteoarthritis (OA) is a slow progressive disease characterized by metabolic, biochemical, and structural changes in the joint cartilage and surrounding tissues, leading to joint dysfunction. Radiographic examination of the knee joint using weight-bearing techniques provides more accurate information for diagnosing osteoarthritis compared to non-weight-bearing techniques. However, at Muhammadiyah Siti Aminah Hospital Bumiayu, this examination was still performed in a supine position due to limitations in bucky stands and the absence of appropriate fixation devices. This study is aimed to design a fixation device for weight-bearing bilateral knee joint examination and to evaluate the performance of the developed fixation device. Method: This research was a quantitative study with an experimental approach. The researcher designed and built a 4-in-1 fixation assistance device that can support the patient, hold the cassette, provide a platform for lateral projection support, and offer handles for patient safety and comfort. Functionality and performance tests were conducted through questionnaires distributed to 6 radiographers at the Radiology Installation of Muhammadiyah Siti Aminah Hospital Bumiayu. The data were processed and analyzed using the Guttman scale and calculated using appropriate formulas. Results: The functionality test results showed a success rate of 93%, while the performance test achieved 86%. The fixation device could support a load of up to 132 kg and was reported to facilitate the examination process by the majority of respondents. Conclusion: The developed fixation assistance device is deemed suitable for use in weight-bearing bilateral knee joint examinations. It effectively supports the efficiency of radiographers' work and enhances patient comfort, although it is recommended that future developments focus on making the device lighter and incorporating adjustable platforms